Dickens on education - Manning, John, 1912- (Heritage., 1959)
This account of Dickens's interest in education covers his life and times, and his fiction, speeches, articles, and letters, Since our knowledge of Dickens's own schooling in not very extensive, the author has made a careful analysis of Dickens's formal schooling and other experiences that informed his mind.